Function of Simile in Symphony “The Dead” - Alireza Asadi; Sara Hosseini (مطالعات زبانی و بلاغی)
Similarity is one of the arrays of the statement, which by claiming similarity between two or more things, not only illustrate in the form of wisdom in the macro dimension, but also examine the general context of a work can measure the degree of creativity of the writer or poet in the design of this similarity. Take a look at contemporary Persian literature and reviews, the role of similarity in the Persian novels show that in the Persian novels, unlike poems, the impact of such unit of similarity goes beyond and if the overall form and its relation to all the figurines novels reviewed, concepts derived from the fictional works of critics could identify the genre and style of the author. Romance symphony “The Dead” is one of the outstanding works of the 1360s and considered that after a few decades, it is still attractive for the readers. A review of the effect of similarity and its role in the normalization of the novel, shows that we are faced with a tragic novel and grief-ridden atmosphere. Reviews of similarity in this novel, shows that About 73% of these sentences, are symbols of helplessness, depression, loneliness, sadness, violence, despair and the desire to pass and perish which have effect in bringing a major contribution to the tragic structures.